From Sandbags to Systems: Six Decades of Eye Care in Nepal and the Road Ahead - Upadhyay, Madan Prasad; Pant, Aashish Raj; Joshi, Purushottam (Nepalese Journal of Ophthalmology, 2026)
Six decades of eye care in Nepal. A journey of transformation.